Properties and response of composite material with spheroidal superelastic shape memory alloy inclusions subject to three-dimensional stress state - Birman, Victor (Journal of physics. D, Applied physics, 2010)
This communication illustrates the method of evaluation of the stiffness tensor and the stress–strain relationship of a particulate composite material with randomly distributed spheroidal superelastic shape memory alloy (SMA) inclusions that is subject to three-dimensional stresses. The Mori–Tanaka homogenization technique in conjunction with the Tanaka phenomenological SMA theory is applied to develop relations between the properties of the composite material and the applied stresses. In addition, the composite stress–strain loop reflecting hysteresis within the SMA material is generated. It is shown that the energy dissipation within a metal matrix composite with spherical SMA inclusions is comparable to that observed in composites with SMA fibres. The solution is exact within the framework of the assumptions of the Mori–Tanaka and phenomenological SMA theories.